Torrefaction of biomass - Luo, Xun (2011)
Stump biomass is energy rich and stump harvesting for use as fuel become more and more interesting in Sweden. Swedish Forest Agency (2009) has estimated that stump harvesting in Sweden would respond to an annual energy supply of 57 TWh/year. However, stump has not been recognized as a bioenergy resource in Sweden. Suitable methods for pre-treatment of stump are probably of great importance to make it accepted as fuel. It is therefore rewarding to carry out an investigation in this area for stump.